Metabolic Dynamics and Prediction of Gestational Age and Time to Delivery in Pregnant Women - Liang, Liang; Rasmussen, Marie-Louise Hee; Piening, Brian; Shen, Xiaotao; Chen, Songjie; Röst, Hannes; Snyder, John K.; Tibshirani, Robert; Skotte, Line; Lee, Norman CY; Contrepois, Kévin; Feenstra, Bjarke; et al. (Cell, 2020)
Metabolism during pregnancy is a dynamic and precisely programmed process, the failure of which can bring devastating consequences to the mother and fetus. To define a high-resolution temporal profile of metabolites during healthy pregnancy, we analyzed the untargeted metabolome of 784 weekly blood samples from 30 pregnant women. Broad changes and a highly choreographed profile were revealed: 4,995 metabolic features (of 9,651 total), 460 annotated compounds (of 687 total), and 34 human metabolic pathways (of 48 total) were significantly changed during pregnancy. Using linear models, we built a metabolic clock with five metabolites that time gestational age in high accordance with ultrasound (R = 0.92). Furthermore, two to three metabolites can identify when labor occurs (time to delivery within two, four, and eight weeks, AUROC ≥ 0.85). Our study represents a weekly characterization of the human pregnancy metabolome, providing a high-resolution landscape for understanding pregnancy with potential clinical utilities. [Display omitted] •Weekly metabolome of maternal blood changes dynamically through healthy pregnancy•A metabolic clock of five blood metabolites accurately predicts gestational age•Two to three metabolites identify labor onset within two, four, and eight weeks•Women with metabolic clocks that outpaced ultrasound evaluation tend to deliver earlier Identification of blood metabolites in pregnant women that can accurately predict gestational age and provide insights into pregnancy variations undetected by ultrasound.